2013
DOI: 10.1093/cvr/cvt079
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection by the TSPO ligand 4′-chlorodiazepam is associated with inhibition of mitochondrial accumulation of cholesterol at reperfusion

Abstract: AimsThe translocator protein (TSPO) is located on the outer mitochondrial membrane where it is responsible for the uptake of cholesterol into mitochondria of steroidogenic organs. TSPO is also present in the heart where its role remains uncertain. We recently showed that TSPO ligands reduced infarct size and improved mitochondrial functions after ischaemia-reperfusion. This study, thus, sought to determine whether cholesterol could play a role in the cardioprotective effect of TSPO ligands. Methods and results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…Administration of the selective TSPO ligands inhibited oxidative stress, improved mitochondrial function, and abolished both mitochondrial cholesterol accumulation and oxysterol production induced by ischaemia–reperfusion. These data showed that reduction of cholesterol accumulation in heart mitochondria by modulation of TSPO activity prevents mitochondrial injury (Paradis et al 2013). To the best of our knowledge, the effect of exercise on the action of TSPO in the heart has not been shown.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Administration of the selective TSPO ligands inhibited oxidative stress, improved mitochondrial function, and abolished both mitochondrial cholesterol accumulation and oxysterol production induced by ischaemia–reperfusion. These data showed that reduction of cholesterol accumulation in heart mitochondria by modulation of TSPO activity prevents mitochondrial injury (Paradis et al 2013). To the best of our knowledge, the effect of exercise on the action of TSPO in the heart has not been shown.…”
Section: Discussionmentioning
confidence: 97%
“…The mechanism responsible for removal of cholesterol from mitochondrial membranes remains unknown, but involvement of 18 kDa mitochondrial translocator protein (TSPO) in this mechanism must be taken into consideration. This protein is responsible for the uptake of cholesterol into mitochondria of steroidogenic organs, but also in heart (Paradis et al 2013). Also, as an element of the mitochondrial outer membrane, cholesterol is associated with the outer/inner mitochondrial membrane contact sites (Rone et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The cardiac damage inflicted by ischemia-reperfusion damage is accompanied by an increase in cholesterol uptake by mitochondria and the generation of auto-oxidized oxysterols, a phenomenon that can be avoided by ligands of translocator protein (18kDa) (TSPO), an OMM protein that interacts with VDAC1 and has been suggested to regulate MPT (123). …”
Section: Metabolic Checkpoints In Cell Fate: Signals Sensors Transdmentioning
confidence: 99%
“…Other studies have associated the effects of TSPO-binding chemicals with membrane cholesterol accumulation/modulation [49,50] and steroidogenesis [51], but in the light of our recent shift in understanding, whether these observations are indeed mediated through TSPO is a question that needs confirmation.…”
Section: Box 2 the Mptmentioning
confidence: 99%